Abject joy Paul, prison, and the art of making do - Schellenberg, Ryan S. (Oxford Oxford University Press USA - OSO, 2021)
Abject Joy is a social history of prison in the Greek and Roman world that takes Paul's letter to the Philippians as its focal instance--or, to put it the other way around, a study of Paul's letter to the Philippians that takes the reality of prison as its starting point. Examining ancient perceptions of confinement, and placing this ancient evidence in dialogue with modern prison writing and ethnography, it describes Paul's urgent and unexpectedly joyful letter as a witness to the perplexing art of survival under constraint.
Intro -- Title Page -- Copyright Page -- Dedication -- Contents -- Preface -- Translations and Abbreviations -- Introduction: Paul, Prison, and the Social History of Emotions -- Prison and the Pauline Legend -- Prison Letters and Pauline Incomparability -- "The Characteristic Emotion of the Sage" -- The Body of Paul and the History of Emotions -- Outline and a Note on Comparison -- 1. Far More Imprisonments: Punitive Custody in the Letters of Paul -- Paul and Other Imprisoned Apostles -- Magistrates and Jurisdictions -- Paul in Local Custody -- Writing in Chains -- Plausible Accusations -- Conclusion -- 2. To Die Is Gain: Subjection, Glory, and Paul's Wish for Death -- Prison before the Prison -- Everyday Violence -- Confinement and Subjugation -- A Noble Death? -- To Depart and Be with Christ -- To Die Is Gain -- Conclusion -- 3. Speaking with All Boldness: Prison in the Roman Social Imagination -- Prisoners of War -- Ill-Fated Aristocrats -- Non-Elite Malefactors -- Philosophers, Astrologers, and Other Divine Heralds -- For the Defense of the Gospel -- Conclusion -- 4. I Have Learned to Be Content: Performing the Autarkic Self -- You Can't Always Get What You Want -- Thanks Anyway -- Agency and Abasement -- Performing Indifference -- Conclusion -- 5. Rejoice with Me: The Epistolary Cultivation of Collective Emotion -- Paul Unaffected -- My Joy and Crown -- Joy, Hardship, and Solidarity -- Socio-affective Emotion Regulation -- Conclusion -- Conclusion: The Body of Our Humiliation -- Bibliography -- Index of Ancient Sources -- Index of Authors and Subjects.
Description based on publisher supplied metadata and other sources
Keywords: Imprisonment-Religious aspects-Christianity; Electronic books